Pengaruh stres kerja terhadap kinerja karyawan melalui work-life balance - Mustikasari, Dwi; Frianto, Agus (Jurnal Ilmu Manajemen, 2024)
This research aims to test and analyze the effect of work stress on employee performance through work-life balance in Health Service Institutions. This research uses quantitative research. The sampling technique used non-probability sampling with a saturated sample type, where all population members were sampled as many as 80 Health Agency respondents. The statistical analysis used in this research is Partial Least Square (PLS) with the help of SmartPLS 4.1.0.1 software. The results of this study explain that work stress has a significant positive effect on employee performance, work stress has a large positive effect on work-life balance, work-life balance has a large positive effect on employee performance, and work-life balance successfully mediates the relationship between work stress and the performance of employees. If an institution wants to improve the performance of its employees, then the institution must be able to manage work stress well, which is balanced with the existing work-life balance.